THE KINDS OF QUESTIONS ASKED BY NOVICE TEACHERS IN LEARNING MATHEMATICS - Zahra, Labiba; Kusmayadi, Tri Atmojo; Usodo, Budi (Journal on Mathematics Education)
This study described the kinds of questions asked by novice teachers during mathematics learning process in senior high school. This study used descriptive analysis. The subjects of this study were 2 novice teachers who teach mathematics in 10th grade. The result shows that the frequent questions asked by novice teacher based on the objective were compliance questions, rhetorical questions and sometimes prompting questions and probing questions. The frequent questions asked by novice teacher based on the cognitive process dimension of Revised Bloomâs Taxonomy were questions of remembering, questions of understanding, questions of applying, questions of analyzing and questions of evaluating. The novice teacher asked the routine questions which had same thinking level. The question with the highest level in thinking didnât ask by the novice teacher.Â